Controlling Depression and Improving Self-Introspection Ability in Post Pandemi Covid-19 Disposal Victims Through Cognitive Thought Stopping Therapy in Agroindustrial Area - Evy Aristawati; Bagus Dwi Cahyono; Nurul Huda (Sekolah Tinggi Ilmu Kesehatan Kendal, 2024)
Employees mental unpreparedness due to termination of employment (PHK) causes depression and lack of self-control which has an impact on social relations problems for those concerned and their environment. Efforts are needed to overcome these problems through psychosocial therapy, including Cognitive Therapy and Thought Stopping Therapy or a synthesis of both to reduce depression and lack of self-introspection for layoff victims. This research aims to overcome depression problems and improve your capacity for mental self-control. This study has an experimental pre-post test design with a control group, the sampling technique is purposive. The sample size is 48 respondents were split into four groups. The duration of the study was 2 months, with the method of observing and giving therapy to layoff victims who had depression and lacked the capacity for introspect. Based on the Wilcoxon test, the results obtained were p = 0.003, Cognitive Therapy (CT) p = 0.003, Thought Stopping (TS) p = 0.002, the value was less than p 0.005 which means it was very significant because there were differences in the results in the treatment and control groups. Post-treatment Kruskal Wallis test on depression variable obtained p = 0.001. The Wilcoxon test on the variable Cognitive Thought Stopping Therapy (CTST) obtained a value of p = 0.002, Cognitive Therapy (CT) p = 0.003, Thought Stopping (TS) p = 0.002 meaning that there is a significant difference in value for each variable measured. The capacity for control negative ideas based on the Kruskal Wallis test p = 0.000. The results of the study explain that there is a significant effect of CTST on reducing the level of depression and increasing the ability of self-introspection in victims of layoffs after the Covid-19 pandemic in the agro-industry area.